PENGARUH MOTIVATIONAL BONUSES, CORPORATE GOVERNANCE, RASIO KEUANGAN, DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA (Jurnal Ekonomi : Journal of Economic, 2022)
The research was aimed to investigate the influence of motivational bonuses, leverage, firm size, size of audit committee, independent commissioners, institutional ownership, managerial ownership, free cash flow, and firm growth as independent variables to earnings management as a dependent variable. This study uses non-financial companies listed on Indonesia Stock Exchange during 2016 to 2020 as the population. The data used in this study is secondary data with purposive sampling method. There are 64 companies, which have 320 data meet the criteria. The Earnings Management level was measured using discretionary accruals calculated using the Modified Jones Model. A multiple linear regression is employed to analyze the data using SPSS 25 version. The empirical results indicate that motivational bonuses, leverage, firm size, institutional ownership, managerial ownership, free cash flow, firm growth have influence to earnings management, while other independents such as size of audit committee, independent commissioners, and managerial ownership have no influence to earnings management practice in the company.